FORMATION OF THE CONCEPT OF A CIRCULAR ECONOMY - Gureva, Maria; Deviatkova, Yulia (Revista Inclusiones, 2021)
The article represents a historical survey describing appearing and development of circular economy as an independent concept and its interсonnection to the phenomenon of new industrialization. The variety of definitions of the concept “circular economy” given by Russian and foreign scientists are provided in the article, basic approaches to the concept formation are determined. The comparative analysis of basic concepts related to the environmentalism (sustainable development, ecologization, green economy, circular economy) was carried out. The evolutionary development of ecological imperatives that take part in the concept formation is studied; the characteristics of the concept, current state and general development prospects are described. The article is concluded by the clarified definition of “circular economy”. From the point of the author’s view, the circular economy concept is a general approach to promote green growth in countries’ development that allows to overcome global ecological problems and, as a result, to achieve sustainable state of the planet and to save living on the Earth.